Human keratinocytes' response to injury upregulates CCL20 and other genes linking innate and adaptive immunity - Kennedy-Crispin, Milène (2011)
In the early stages of wound healing, keratinocytes become “activated” and release inflammatory molecules such as interleukin-1 and interleukin-8 that are linked to innate immune responses and neutrophil recruitment. It is unclear, however, whether keratinocytes release molecules linked to adaptive immune responses, e.g. CCL20, in their early state of activation without signals from infiltrating T cells. This study aims to isolate the immediate alterations in protective and inflammatory gene expression that occur in epidermal keratinocytes, with a particular focus on molecules associated with cell-mediated immunity. We used dispase-separated epidermis, followed by intercellular disassociation by trypsinization, as a model for epidermal injury. We obtained a pure population of keratinocytes using flow cytometry. As a control for uninjured epidermis, we performed laser capture microdissection on normal human skin. Sorted keratinocytes had an early burst of upregulated gene expression, which included CCL20, IL-15, IL-23A, IFN-κ, and several antimicrobial peptides. Our results provide insight into the potential role of keratinocytes as contributors to cell-mediated inflammation, and expand knowledge about gene modulation that occurs during early wound healing. Our findings may be relevant to cutaneous diseases such as psoriasis, where micro-injury can trigger the formation of psoriatic plaques at the site of trauma.